PENDIDIKAN BERBASIS ADAB MENURUT A. HASSAN - Syarif Hidayat Busthami (Jurnal Pendidikan Agama Islam, 2018)
Abstract This writing discusses and analyzes A. Hassan’s concept in education that is courtesy based educational concept. The figure of A Hassan is often connected with his hard works in spreading the religion guidance that based on Quran and Sunnah besides his concern on education. The research uses qualitative critical analysis method on his works / books and interviews with figures who know and deal with the concept in Persis. The writer conclude that A. Hasssan’s educational concept emphasized courtesy or known as character education. Not only created and educate to be tafaquh fi al-din but also be prepared to be strong/ discipline and polite person. Abstrak Tulisan ini menyajikan analisis mengenai pendidikan berbasis adab A. Hassan. Seringkali ketokohan A. Hassan sebagai guru utama Persatuan Islam dinilai dari sisi kegigihan dalam menegakkan al-Qur’an dan al-Sunnah. Padahal, kefiguran beliau berkaitan pula dengan dunia pendidikan. Penelitian ini menggunakan pendekatan kualitatif dengan bentuk anialisis terhadap karya-karya A. Hassan dan wawancara kepada tokoh-tokoh Persatuan Islam. Penulis menyimpulkan, pendidikan A. Hassan banyak menekankan pada pendidikan adab yang dikenal dewasa ini dengan istilah pendidikan karakter. Bukan sekedar mendidik siswa untuk memahami ajaran dengan benar (tafaqquh fi al-din) namun juga mendidik supaya mereka menjadi manusia yang bisa disiplin dan beradab.